Spain. Telephone conversation : Memorandum of interview; Miss Mcdonald, Mr. Attlee's secretary - McDonald, Florence
016a-0054-001 MEMORANDUM OF INTERVIEW. Date 18th March, 1937. Time to Reference FEM/MT/663 Present Miss McDonald Mr. Attlee's Secretary. SUBJECT. SPAIN. Telephone Conversation. I telephoned Mr. Attlee on behalf of Sir Walter Citrine. Mr. Attlee was not there so I spoke to his Secretary. I said that Sir Walter would like to have spoken direct to Mr. Attlee but he had a series of meetings and deputations. Our Council thought they should send a deputation to Mr. Eden and thought it might be preferable for this to be confined to the Council. It would leave the Parliamentary Labour Party free to have a tilt in Parliament without feeling that they were tied by any talk they had had with the Minister. Mr. Middleton and Dr. Dalton agreed with the suggestion but Sir Walter wanted to consult Mr. Attlee. The points they would make to the Government would be that they have not taken effective enough action on Spain. They had not made sufficient protest on the pouring in to Spain of German and Italian troops, and we had reason to believe even now cargoes were being loaded in Bremen for Franco. The Secretary 'phoned me the same morning to say that Mr. Attlee thought it was a very good idea that the Council should send their own deputation. It was the Parliamentary Party's job to see to the matter in the House. 292/946/16a/55